Perbandingan Pergerakan Titik Pantau Deformasi Kepulauan Sangihe Menggunakan Metode Perhitungan Periodik dan Simultan Berdasarkan Data GNSS Tahun 2014, 2015, dan 2016 - Fauzi, Muhammad Arsyad; Heliani, Leni Sophia (Universitas Gadjah Mada, 2020)
The study of deformation monitoring point movement of Sangihe Islands was conducted using the GNSS measurement methods. One of the factor that determines the accuracy of the deformation monitoring is the utilized data processing methods. Therefore, this research analyze the comparison of deformation monitoring point movement of Sangihe Islands using periodic and simultaneous GNSS data processing methods. This research used three observations epochs of GNSS, i.e. 2014, 2015 and 2016. The observational data were processed using GAMIT/GLOBK software that tied to ITRF 2014 to produce coordinates and their accuracy. Based on the coordinate data and its accuracy, the velocity of movements calculation and their accuracy was done using the periodic and simultaneous methods. Based on the periodic method, the velocity of the SGH1 point on the N component is -1,11 ± 2,72 mm/year, on the E component is 9,21 ± 4,17 mm/year, and on the U component is -15,02 ± 50,64 mm/year, while the velocity of the SGH3 point on the N component is -4,93 ± 1,56 mm/year, on the E component is 16,50 ± 2,47 mm/year, and on the U component is -6,69 ± 19,42 mm/year. Based on the simultaneous method, the velocity of the SGH1 point on the N component is -1,56 ± 1,25 mm/year, on the E component is 9,40 ± 1,55 mm/year, and on the U component is -11,54 ± 5,83 mm/year, while the velocity of the SGH3 point on the N component is -5,18 ± 0,88 mm/year, on the E component is 16,91 ± 1,10 mm/year, and on the U component is -2,84 ± 3,49 mm/year. This research proves the hypothesis that the simultaneous GNSS data calculation results in higher accuracy than the periodic method.